c-Jun N-terminal Kinase (JNK) Signaling as a Therapeutic Target for Alzheimer’s Disease - Yarza, Ramon; Vela, Silvia; Solas, Maite; Ramirez, Maria J. (Frontiers in Pharmacology, 2016)
c-Jun N-terminal kinases (JNKs) are a family of protein kinases that play a central role in stress signaling pathways implicated in gene expression, neuronal plasticity, regeneration, cell death and regulation of cellular senescence. It has been shown that there is a JNK pathway activation after exposure to different stressing factors, including cytokines, growth factors, oxidative stress, unfolded protein response signals or A peptides. Altogether, JNKs have become a focus of screening strategies searching for new therapeutic approaches to diabetes, cancer or liver diseases. In addition, activation of JNK has been identified as a key element responsible for the regulation of apoptotic apoptosis signals and therefore, it is critical for pathological occurring cell death associated with neurodegenerative diseases and, among them, with Alzheimer's disease (AD). In addition, in vitro and in vivo studies have reported alterations of JNK pathways potentially associated with pathogenesis and neuronal death in AD. JNK’s, particularly JNK3, not only enhance Aβ production, moreover it plays a key role in the maturation and development of neurofibrillary tangles. This review aims to explain the rationale behind testing therapies based on inhibition of JNK signalling for AD in terms of current knowledge about the pathophysiology of the disease. Keeping in mind that JNK3 is specifically expressed in the brain and activated by stress-stimuli, it is possible to hypothesize that inhibition of JNK3 might be considered as a potential target for treating neurodegenerative mechanisms associated with AD.